Characterisctics, Clinical Features, And Management Of Fibroadenoma Mammae Patients At Dustira Hospital Cimahi - Ris Kristiana; Salsha Regina Syakyra; Endah Hamidah; Endry Septiadi; Fitriardi Sejati; Tatang Bisri (Jurnal EduHealth, 2025)
Fibroadenoma mammae (FAM) is the most common benign breast tumor that occurs at the age of 14-35 years. About 10% of the female population has FAM. FAM manifests as solitary masses that are easily movable, well-defined, with a smooth surface. The aim of this study was to determine the characteristics, clinical features, and management of FAM patients at Dustira Hospital using secondary data from medical records. A total of 68 FAM patients were selected as samples during the period 2018-2023. The research variables consisted of the number of cases, age, body mass index(BMI), location, topography, size, quantity, and management of FAM. Univariate analysis was used in this study and the results were presented in narrative and tabular forms. The results of the study showed that the highest number of FAM cases occurred in 2018, reaching 28 (41.1%). Characteristics of FAM patients included 49 individuals (72%) in the 16-30 age group, 32 individuals (47%) with normal body mass index. Clinical features of FAM were found in 31 individuals (45.6%) on the right breast, 24 individuals (35.3%) in the upper medial quadrant, with a size of 3-5 cm in 24 individuals (35.3%), and 49 individuals ( 72.1%) limited solitary masses. Management included surgery in all 68 individuals (100%), with 67 individuals (98.5%) underwent excision, while 1 individual (1.5%) underwent incision. Age and BMI are suspected to play a role in FAM formation related to estrogen hypersensitivity and mutations in the mediator complex subunit 12 (MED12). Lesion size is influenced by estrogen exposure. Management of fibroadenoma depends on the patient's preferences and clinical conditions. Women at risk or suspecting breast masses are advised to perform self-breast examination (BSE) and efficiently consult with healthcare professionals.